2010
DOI: 10.1177/1947601910364227
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Suppressor Protein Pdcd4 With Ribosomes Is Mediated by Protein-Protein and Protein-RNA Interactions

Abstract: The Pdcd4 (programmed cell death gene 4) gene has been implicated as a novel tumor suppressor gene in the development of several types of human cancer. The Pdcd4 protein is believed to act as a translation suppressor of mRNAs containing structured 5′ UTRs. Pdcd4 contains 2 copies of so-called MA3 domains that mediate tight interactions with the translation initiation factor eIF4A, resulting in the inhibition of the eIF4A helicase activity. The N-terminal part of Pdcd4, which has been less well characterized, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Initially, in vitro binding experiments using nonspecific RNA suggested that the N-terminal part of Pdcd4 is involved in RNA binding (Bo¨hm et al, 2003). More recently, we have shown that the Pdcd4 RNAbinding domain is required for the association of Pdcd4 with ribosomal complexes in vivo, providing the first evidence for a role of RNA binding in targeting Pdcd4 to the translation machinery (Wedeken et al, 2010). The identification of a 'Pdcd4-response region' in c-myb mRNA has allowed, for the first time, to study RNA binding of Pdcd4 in the context of a physiological RNA target site.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Initially, in vitro binding experiments using nonspecific RNA suggested that the N-terminal part of Pdcd4 is involved in RNA binding (Bo¨hm et al, 2003). More recently, we have shown that the Pdcd4 RNAbinding domain is required for the association of Pdcd4 with ribosomal complexes in vivo, providing the first evidence for a role of RNA binding in targeting Pdcd4 to the translation machinery (Wedeken et al, 2010). The identification of a 'Pdcd4-response region' in c-myb mRNA has allowed, for the first time, to study RNA binding of Pdcd4 in the context of a physiological RNA target site.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the amino terminal domain of Pdcd4 binds to RNA and that its RNA-binding activity is mediated by two clusters of basic amino acids. Mutation of both clusters (which are referred to as RBM1 and 2) results in a complete loss of the RNAbinding activity (Bo¨hm et al, 2003;Wedeken et al, 2010). As shown in Figure 5, mutant Pdcd4 carrying mutations of the basic amino acid clusters inhibited c-Myb translation less strongly than wild-type Pdcd4, Nco, E, X, N, S and B refer to restriction sites for NcoI, EcoRI, XmaI, NaeI, SalI and BglII, respectively.…”
Section: C-myb Mrna Is a Translational Target Of Pdcd4mentioning
confidence: 99%
See 3 more Smart Citations